Efektivitas Pelaksanaan Batas Usia Minimal Perkawinan Berdasarkan Undang-Undang Perkawinan Di Kabupaten Bone - Ririn Yulandari Abbas; Syahruddin Nawi; Dachran S. Busthami (ILIN Institute, 2021)
The research objective to analyze the effectiveness of implementing the minimum age limit for marriage in Bone Regency based on Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage and the factors that influence it. The research method in this study uses the type of empirical research. The results of this study indicate that: (1) the effectiveness of implementing the minimum age limit for marriage in Bone Regency based on Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage is less effective; (2) the factors that affect the effectiveness of the implementation of the minimum age limit for marriage in Bone Regency are factors of legal substance, legal structure, legal culture, society, facilities and infrastructure, promiscuity, economy, and educational factors. Tujuan penelitian menganalisis efektivitas pelaksanaan batas usia minimal perkawinan di Kabupaten Bone berdasarkan Undang-Undang Nomor 16 Tahun 2019 tentang perubahan atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan faktor-faktor yang mempengaruhinya. Metode penelitian dalam penelitian ini menggunakan tipe penelitian empiris. Hasil penelitian ini menunjukkan bahwa: (1) efektivitas pelaksanaan batas usia minimal perkawinan di Kabupaten Bone berdasarkan Undang-Undang Nomor 16 Tahun 2019 tentang perubahan atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan berjalan kurang efektif; (2) faktor-faktor yang mempengaruhi efektivitas pelaksanaan batas usia minimal perkawinan di Kabupaten Bone yaitu faktor substansi hukum, struktur hukum, budaya hukum, masyarakat, sarana dan prasarana, pergaulan bebas, ekonomi, dan faktor pendidikan.